2014
DOI: 10.1111/pin.12177
|View full text |Cite
|
Sign up to set email alerts
|

Coronary triglyceride deposition in contemporary advanced diabetics

Abstract: It is of importance to clarify pathophysiology of diabetic heart diseases such as heart failure and coronary artery disease. We reported a novel clinical phenotype called triglyceride deposit cardiomyovasculopathy (TGCV), showing aberrant TG accumulation in both coronary arteries and myocardium, in a cardiac transplant recipient. Here, we examined autopsied diabetics for TG deposition in cardiovasculature. Consecutive series of hearts from advanced diabetes mellitus (DM) subjects (DM group: DMG, n = 20) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…4) (13,14). As with primary TGCV, patients with idiopathic TGCV also exhibit triglyceride accumulation in cardiac muscle and …”
Section: Idiopathic Tgcvmentioning
confidence: 99%
See 1 more Smart Citation
“…4) (13,14). As with primary TGCV, patients with idiopathic TGCV also exhibit triglyceride accumulation in cardiac muscle and …”
Section: Idiopathic Tgcvmentioning
confidence: 99%
“…Human genetic ATGL deficiency (10,11) has turned out to be ultra-rare (12) and only 47 patients identified globally, since we launched the Japan TGCV study group in 2009. However, our postmortem analyses (13,14) for subjects who died of cardiovascular diseases demonstrated that substantial numbers of autopsied individuals showed TGCV phenotype, most of who had suffered from diabetes mellitus. The amount of triglycerides in the coronary artery of patients who died of cardiovascular complications was several times higher in diabetic patients than in non-diabetic patients.…”
Section: T Riglyceride Deposit Cardiomyovasculopathy (Tgcv) Is Amentioning
confidence: 99%
“…Furthermore, because a mild reduction of BMIPP WOR was reported in chronic hemodialysis patients (18), it would be of interest to know whether TGCV phenotype might exist among patients with chronic kidney disease, as reported in our postmortem study (6).…”
Section: Differential Diagnosis Of Tgcvmentioning
confidence: 68%
“…Genetic causes and etiologies of the latter are unknown. I-TGCV was initially identified in the autopsied study with diabetic patients (6) and we recently reported that ATGL activities in peripheral leukocytes were markedly reduced in some patients with I-TGCV (7). In TGCV, abnormal metabolism of intracellular TG and LCFA such as ATGL dysfunction leads to lipotoxicity and energy failure in affected cells and tissues, resulting in HF, CAD, and arrhythmia (3,7).…”
Section: Definition Classification and Pathophysiology Of Tgcvmentioning
confidence: 99%
“…Cholesterol is a vital causal factor and focus of research for heart diseases; however the involvement of triglycerides remains unclear. It has been shown that massive accumulation of triglycerides was noted in coronary atherosclerotic lesions as well as in the myocardium and named as phenotype "triglyceride deposit cardio myovasculopathy (TGCV)" and they are identified as homozygous for a genetic mutation in the adipose triglyceride lipase (ATGL), an essential molecule for hydrolysis of intracellular triglycerides 18 .…”
Section: Triglcerides In Dmmentioning
confidence: 99%